Experience Effects on the Development of Late Second Language Learners' Oral Proficiency. Issue 3 (21st May 2015) - Saito, Kazuya
<x xml:space="preserve">Abstract</x> The aim of this study was to evaluate the effects of second language (L2) experience–operationalized as length of residence (LOR) in Canada—on late Japanese learners of English. Data collected from 65 participants consisted of three groups of learners (short‐, mid‐, and long‐LOR groups) and two baseline groups of native Japanese and native English speakers, with 13 participants in each group. The global quality of the participants' spontaneous speech production was initially judged by 10 native‐speaking English raters for accentedness (linguistic nativelikeness) and comprehensibility (ease of understanding) and then submitted to segmental, prosodic, temporal, lexical, and grammatical analyses. According to the results, LOR was generally predictive of improved comprehensibility through its association with adequate and varied prosody, optimal speech rate, and proper lexicogrammar usage. In contrast, contributions of LOR to accentedness remained unclear, with less accented speech linked to refined segmental accuracy, vocabulary richness, and grammatical complexity. These findings suggest that learners continue to improve in their L2 oral proficiency over an extensive period of L2 immersion (e.g., 6 years of LOR), and they likely do so by paying selective attention to certain linguistic domains closely linked to comprehensibility—but not necessarily relevant to accentedness—for the purpose of successful L2 communication.